Glimpse of Medical Support and Healthcare in Peacekeeping Mission: Experience from United Nations Mission in Liberia - Kunwar, Mandeep (Medical Journal of Shree Birendra Hospital, 2016)
Nepal has been actively participating in different United Nations (UN) peacekeeping missions for a long time. Medical care in peacekeeping and humanitarian mission consists of different approach than what is seen in regular clinical and hospital setting. This article shares some of the healthcare aspects and medical activities carried out during deployment of Nepalese peacekeepers to such UN mission.